Comparative analysis of aerodynamic characteristics of centrifugal dust collectors under parallel comparison testing - Natalia N. Azimova; Yury I. Bulygin; Irina S. Kuptsova (Advanced Engineering Research)
Introduction. The article is devoted to investigations on the “Cyclone” semi-industrial pilot plant which allows for parallel comparative aerodynamic testing of the cylindrical cyclone with “TsN-15u-300” volute and the patented cyclone with the “CSC-200-300” inverted cone. The work objective is to obtain experimentally major aerodynamic characteristics of the centrifugal dust collectors of various shapes without bunkers under the parallel comparative testing with the subsequent analysis of the results. Improving the efficiency, increasing the productivity while reducing the energy consumption for ventilation systems and metal consumption for centrifugal dust collectors, are crucial technological tasks. Materials and Methods . Parallel comparative aerodynamic testing of centrifugal dust collectors of various shapes for the cylindrical cyclone with “TsN-15u-300” volute and the patented cyclone with the “CSC-200-300” inverted cone is conducted. At this, Pitot tubes and two high-precision Testo -521 differential pressure gauges are used. Mathematical calculations of the hydraulic resistance coefficients for the investigated devices are made. Research Results. As a result of the experiments, the behavior of the total pressures and air velocity at various gage points of the inlet and outlet nozzle sections of the cyclone apparatus at different capacities of the fan exhauster is specified. The calculated hydraulic resistance coefficients (HRC) of the “CSC-200-300” device appear 2-2.2 times lower than HRC of “TsN-15u-300” due to the higher flow velocity in the device body. This indicates its best aerodynamics and possibly higher efficiency of the dust collection due to the high flow turbulence. Discussion and Conclusions . The obtained aerodynamic characteristics are used in operation to assess the effectiveness and economic benefits of the cyclone apparatus. Further experimental studies on the pilot plant are needed to verify the conclusions.